60.5k views
1 vote
For f(x)=3x+1 and g(x)=x^2-6, find (f o g)(x)

User Shushana
by
7.1k points

2 Answers

4 votes
The answer is: " 3x² − 17 " .
______________________________________
f(x) = 3x + 1 ;
________________________________________________
If g(x) = x² − 6 ;

then: (f o g)(x) = f(x² − 6) = 3x + 1 ;

= 3(x² − 6) + 1 = 3x² − 18 + 1 ;

= 3x² − 17 .
_______________________________________________
User Gagarwal
by
6.1k points
4 votes

Answer:

3x^2+x^2-18x-6

Explanation:

User Havexz
by
6.4k points